The Influence of Financial Distress, Leverage, Firm Size, and Profitability on Accounting Conservatism - Dinan Fathi Shiddieqy; Prasojo, Prasojo; Utami, Ristianawati Dwi (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2023)
Purpose: This study aims to examine and analyze the effect of financial distress, leverage, firm size, and profitability on accounting conservatism. Methodology: The research sample this time is manufacturing companies listed on the Indonesian sharia stock index for 2017–2021. The method used in this study is panel data regression. This study uses the Fixed Effect Model as the best model in the study. Findings: This test found that the variables financial distress and profitability have a significant positive effect on accounting conservatism. Meanwhile, leverage and firm size have no effect on accounting conservatism. Novelty: This study continues previous research by using different samples and populations and adding an independent variable.